Prognostic Value of Serum Copper for Post-Stroke Clinical Recovery: A Pilot Study - Squitti, Rosanna; Siotto, Mariacristina; Assenza, Giovanni; Giannantoni, Nadia M.; Rongioletti, Mauro; Zappasodi, Filippo; Tecchio, Franca (Frontiers in Neurology, 2018)
The clinical course after ischemic stroke can vary considerably despite similar lesions and clinical status at the onset of symptoms, suggesting that individual factors modulate clinical recovery. Here, we sought to test the working hypothesis that elevated copper values provide prognostic information, and specifically predict worse clinical recovery. We further sought to support previous findings regarding metal metabolism in acute stroke. We assessed total antioxidant status, oxidative stress factors (peroxides) and metal metabolism markers (iron, copper, ceruloplasmin concentration and activity, ferritin and transferrin) in the acute phase (2-10 days from symptom onset) in 30 patients affected by unilateral middle cerebral artery (MCA) stroke. A longitudinal assessment of clinical deficit was performed in the acute and stabilized phases (typically 6 months post-stroke) using the National Institute of Health Stroke Scale (NIHSS). In identifying recovery-related factors, we considered Effective Recovery, calculated as the ratio between actual NIHSS recovery and the total potential recovery. This allows an estimation of the actual recovery adjusted for the patient’s initial condition. In the acute phase, clinical severity was correlated with increased peroxide concentrations, and lower iron levels. Less successful clinical recovery was correlated with increased acute copper levels, which entered a multiple regression model that explained 24% of Effective Recovery variance. These pilot data suggest that, in the acute phase of an ischemic stroke, copper may provide useful information about clinical recovery.